Heat and mass transmission through the nanofluids flow subject to exponential heat source/sink and thermal convective condition across Riga plates - Ali, Bilal; Jubair, Sidra; Fouly, Ahmed (Chemical engineering research & design, 2024)
The analysis of the squeezing nanofluid flow across bounded domains received great attention from researchers and engineers due to its tremendous application in automobiles, energy exchangers, and aerodynamics. In the current analysis, we are using double Riga plates parallel to each other, in order to induce the squeezing nanofluids flow with the significances of chemical reaction, thermal radiation, and heat source/sink. The nanoliquid has been prepared by the dispersion of Copper (Cu) nanoparticles (NPs) in kerosene oil (C12H26C15H32) and water (H2O). The nanofluid flow has been modeled in form of nonlinear partial differential equations, which are further convert into the dimensionless form of ordinary differential equations. The obtained set of non-dimensional equations is numerically resolved by using the Matlab built-in package bvp4c. The results are compared to another numerical technique for accuracy purposes. The detailed results are presented in Figures. It has been detected that the energy field of nanofluid is enriched with the effect of heat source/sink component. Moreover, the velocity curve magnifies with the variation of the squeezing parameter of Riga plates, whereas declines with the accumulation of Cu-NPs in both types of base fluid (C12H26C15H32 and H2O). [Display omitted] •Numerical to analysis on squeezing nanoliquid flow across parallel Riga plates.•Squeezing nanofluids flow with energy and mass transference has been examined.•The nanoliquid has been prepared by the dispersion of Cu-NPs in C12H26C15H32 and H2O.•The nanoliquid flow model was 1st simplified to non-dimensional form and then numerically elucidated through the bvp4c package.•The results are compared to the ND-solve technique for accuracy purposes.